PROCESSES OF PREPARING EDUCATORS FOR SCHOOL EDUCATION IN PRE-SCHOOL EDUCATION ORGANIZATIONS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In this article, it is noted that parents form the personality of children from an early age, how incomparable is the role of parents in the development of their children, their place in society, and the formation of a sense of humanity in their hearts. and it is shown that parents should have more moral, legal, pedagogical and psychological knowledge and, most importantly, practical skills.